Effectivenessof Micro-Influencer Collaboration on Engagement and Brand Awareness: A Case Study of the Instagram Account of LSPDitekindo (@ditekindo) - Aurelia Widya Astuti; Satrio Rafli Firmansah; Mamduh Rihadatul Aisy; Rega Slamet Riyadi (Al-Makki Publisher, 2025)
Professional Certification Institutions (LSP) require effective digital communication strategies to reach their target audiences in the digital age. LSP Ditekindo's Instagram performance is not yet optimal, with low engagement rates and limited awareness conversion, thus requiring the right influencer collaboration strategy. This study aims to identify and describe the collaboration strategy between LSP Ditekindo and influencers in improving Instagram account performance, as well as evaluate the effectiveness of collaborative content in building engagement and brand awareness. The study uses a mixed-method approach, collecting quantitative data from Instagram Insights and qualitative data through interviews. The analysis was conducted using a descriptive comparative method, calculating the engagement rate using the formula (Total Interactions/Total Reach & Impressions) × 100%. The collaboration with influencer Lukman Acep Nul Hakim resulted in significant improvements: followers increased by 190 (0.81%), likes surged by 5,050%, Reach & Impressions rose by 277%, and the total engagement rate increased from 0.02% to 4.78%. LSP Ditekindo achieved an “Excellent” status across three industry benchmarking indicators in the B2B sector. The results validate the Trust Transfer Theory, Social Proof Theory, and Uses and Gratifications Theory, with key success factors including the accuracy of influencer selection, the authenticity of message delivery, and strategic timing.